Differentiating Permit Allocation Across Areas - Zamorano-Ford, J (GENES (Groupe des Ecoles en Economie et Statistiques), 2019)
This paper addresses the issue of differentiating permit allocation across areas, this being linked to the possibility of firms to relocate. Two different areas are considered: a domestic area where a cap-and-trade system is implemented and a foreign area where there is no environmental regulation. In addition, the domestic area is divided into a coastal area , close to the border and an inland area , further from the border. The conditions under which welfare decreases with relocation are determined. In such a case, free allowances may be used to prevent firms from relocating. One option to minimize the cost of preventing firms from relocating could be to differentiate permit allocation across areas. However, differentiating subsidies in the same sector is a politically sensitive initiative and the competition authorities may be reluctant to implement such a policy. Nevertheless, the paper shows that the firms that receive less allowances would also benefit from the subsidies granted to the other firms. Indeed, we demonstrate that in such a context the relocation of domestic firms to a foreign country reduces the profits of the remaining domestic firms. © 2018 GENES (Groupe des Ecoles en Economie et Statistiques). All rights reserved.